2015
DOI: 10.1002/hep.27343
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathophysiology of portal hypertension

Abstract: Over the past two decades the advances in molecular cell biology have led to significant discoveries about the pathophysiology of portal hypertension (PHT). In particular, great progress has been made in the study of the molecular and cellular mechanisms that regulate the increased intrahepatic vascular resistance (IHVR) in cirrhosis. We now know that the increased IHVR is not irreversible, but that both the structural component caused by fibrosis and the active component caused by hepatic sinusoidal constrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 94 publications
(155 reference statements)
3
113
0
Order By: Relevance
“…We think that PAI-1 4G-4G and MTHFR 677TT can increase the inflammation response, participating to the activation of perisinusoidal hepatic stellate cells, causing hepatic fibrosis and augmented intrahepatic vascular resistance typical of the LC, as suggested by Fernandez. 13 V Leiden 506Q was significantly correlated with BCS patients (13/45 patients), confirming other previous articles on BCS, 14,15 but Hardy-Weinberg equilibrium for V Leiden 506Q was respected both in patients with SVT and in HC.…”
Section: Discussionsupporting
confidence: 89%
“…We think that PAI-1 4G-4G and MTHFR 677TT can increase the inflammation response, participating to the activation of perisinusoidal hepatic stellate cells, causing hepatic fibrosis and augmented intrahepatic vascular resistance typical of the LC, as suggested by Fernandez. 13 V Leiden 506Q was significantly correlated with BCS patients (13/45 patients), confirming other previous articles on BCS, 14,15 but Hardy-Weinberg equilibrium for V Leiden 506Q was respected both in patients with SVT and in HC.…”
Section: Discussionsupporting
confidence: 89%
“…We suppose that PAI-1 4G-4G and MTHFR 677TT may increase the inflammation response, participating in the activation of perisinusoidal stellate cells, causing hepatic fibrosis and augmented intrahepatic vascular resistance in cirrhosis, as suggested by Fernandez (Fernandez, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Portal hypertension (PHT) is a major complication of liver cirrhosis, which signifies a leading cause for mortality and transplantation [22]. Recent studies considered angiogenesis as an important pathophysiological feature of PHT [23,24]. Furthermore, many studies have demonstrated that angiogenesis inhibitory drugs may be effective in reducing portal pressure, which suggests that anti-angiogenesis could be a valuable therapy for PHT [25,26].…”
Section: Discussionmentioning
confidence: 99%